2009
DOI: 10.1021/tx900221s
|View full text |Cite
|
Sign up to set email alerts
|

Natural Polyphenols as Direct Trapping Agents of Lipid Peroxidation-Derived Acrolein and 4-Hydroxy-trans-2-nonenal

Abstract: Acrolein (ACR) and 4-hydroxy-trans-2-nonenal (HNE) are two cytotoxic lipid-derived alpha,beta-unsaturated aldehydes which have been implicated as causative agents in the development of carbonyl stress-associated pathologies. In this study, 21 natural polyphenols were screened to identify effective scavenging agents of ACR and/or HNE in simulated physiological conditions. It was found that flavan-3-ols, theaflavins, cyanomaclurin, and dihydrochalcones effectively trapped ACR and HNE by working as sacrificial nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 39 publications
2
93
1
Order By: Relevance
“…Similar polyphenols have also been documented as effective trapping agents of ACR [118][119][120]. In a screening of 21 natural polyphenols, it was found that nine of them (1 mM) directly quenched ACR (0.5 mM) by 27.4-99.6% under simulated physiological conditions (0.01 M PBS, pH 7.4, 371C) with 90 min incubation.…”
Section: Reactivitymentioning
confidence: 87%
See 1 more Smart Citation
“…Similar polyphenols have also been documented as effective trapping agents of ACR [118][119][120]. In a screening of 21 natural polyphenols, it was found that nine of them (1 mM) directly quenched ACR (0.5 mM) by 27.4-99.6% under simulated physiological conditions (0.01 M PBS, pH 7.4, 371C) with 90 min incubation.…”
Section: Reactivitymentioning
confidence: 87%
“…Examination of the structure-activity relationship showed that a phloroglucinol moiety (usually called an A ring in these structures) was shared among all the effective scavengers, suggesting the importance of this skeleton for trapping of ACR [119]. Furthermore, substitution of any of the hydroxyl groups in A ring weakened the activities for electrophilic aromatic substitution, therefore lowering the trapping effects [120].…”
Section: Reactivitymentioning
confidence: 99%
“…Enolate Hepatoprotection in Ischemia-Reperfusion adducts with acrolein, HNE, and other electrophilic unsaturated aldehydes that participate in oxidative stress-induced injury (LoPachin et al, 2011). Similarly, curcumin and other phytopolyphenols (e.g., phloretin, resveratrol) can ionize to form nucleophilic enolate sites that scavenge electrophilic aldehydes (Awasthi et al, 1996;Zhu et al, 2009Zhu et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidation end-products of sebum and keratinocyte cell membrane lipid moieties represent key biochemical mediators of the inflammatory reaction induced by UV irradiation [1,73,74], among which 4-hydroxynonenal (4-HNE) is the most thoroughly characterised. Green tea polyphenols, theaflavins, and other SPMs could act as sacrificial nucleophiles trapping 4-HNE efficiently, the reason why tea and red wine polyphenols protect various types of cells in vitro, against HNE-induced intracellular oxidative stress and cytotoxicity [75]. In addition, a significant inhibition of HNE-induced mitochondrial ROS production is provided by quercetin, epigallocatechin gallate (EGCG), theaflavins and their gallate esters [76].…”
Section: Effects Of Secondary Plant Metabolites On Immune Responses Tmentioning
confidence: 99%